Gesture-based interfaces for INTEROB: interacting with information and robotics systems - Vatavu, Radu-Daniel; Pentiuc, S.G. (Оптико-електронні інформаційно-енергетичні технології, 2009)
We discuss in this paper several implementations of computer vision applications that were developed in the last two years in our laboratory and for which gesture-based interactions were introduced. The aim is to provide enhanced human-computer interfaces for several commonly encountered application scenarios: manipulating virtual objects and working inside virtual environments, playing computer games and interacting with robotic systems. We particularly focused on table-based systems which allow natural and intuitive interactions as they transform into comfortable and familiar interfaces.